1997
DOI: 10.1038/sj.onc.1200993
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of and effector for metastasis-inducing DNAs from a human metastatic carcinoma cell line

Abstract: Benign rat mammary epithelial cells transfected with restriction enzyme-fragmented DNA from a human malignant metastatic cell line (Ca2-83) produces transfectants that yield metastatic tumours in syngeneic rats. The six metastasis-inducing DNAs (Met-DNAs) that have been isolated from such transfectants are subgene in size and do not code for any expressed mRNAs, but correspond to potential regulatory regions of human DNA from malignant, metastatic cells. In pilot studies the one Met-DNA tested is detectable in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 20 publications
2
56
0
Order By: Relevance
“…[23][24][25][26][27][28][29][30][31] These studies indicated that transfection of genomic DNA from one cell type to another resulted in integration of the exogenous DNA and stable expression of the trans-ferred genes. This was the case for genes specifying missing enzymes, as well as for genes specifying membraneassociated determinants.…”
Section: Fibroblasts Survived Significantly Longer Than Mice In Variomentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31] These studies indicated that transfection of genomic DNA from one cell type to another resulted in integration of the exogenous DNA and stable expression of the trans-ferred genes. This was the case for genes specifying missing enzymes, as well as for genes specifying membraneassociated determinants.…”
Section: Fibroblasts Survived Significantly Longer Than Mice In Variomentioning
confidence: 99%
“…Earlier work on the generation of metastatic variants of Rama 37 cells by transfection of genomic DNA from rat and human breast carcinoma cells confirmed the validity of DNA transfection as a technique with which to assay the metastatic capability of genomic British Journal of Cancer (1998) 77(2), 287-296 DNA fragments (Jamieson et al, 1990a;Davies et al, 1994), as well as that of a variety of cellular oncogenes (Bernstein and Weinberg, 1988), and the gene for calcium-binding protein p9Ka (Jamieson et al, 1990b;Davies et al, 1993). Using this technique, several DNA fragments closely associated with metastasis in human breast cancer cell lines have been identified (Chen et al, 1997). In this system, the transfected DNA responsible for inducing metastasis does not code for growth-promoting oncogenes such as ras etc.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, transfection of similarly fragmented DNA from benign, non-metastasizing mammary epithelial cells does not produce new cell strains with metastatic ability (Davies et al, 1994). Thus, it is transfection of a particular DNA sequence, and not the transfection process itself, that is responsible for the generation of metastatic variants in this model (Chen et al, 1997).…”
mentioning
confidence: 97%
See 2 more Smart Citations